The Satisfaction of Grab Users in Parepare City Using The Structural Equation Model: Kepuasan Pengguna Grab di Kota Parepare Menggunakan Model Persamaan Struktural - Nur Ayatillah; Hakzah; Andriyani; Andi Bustan Didi (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
The challenges faced by the city of Parepare, South Sulawesi, in providing adequate public transportation have led many residents to rely on online transportation services such as Grab. The purpose of this study was to analyze user satisfaction with Grab using Structural Equation Modeling (SEM) version 23. This quantitative research involved a sample of 247 Grab Bike users in Soreang District, with data collected through questionnaires. The analysis included validity and reliability tests as well as model fit assessment. The results indicated that the variables tangible, empathy, reliability, responsiveness, and price had a positive and significant effect on customer satisfaction, while assurance did not. The model fit test revealed that some indices met the criteria, but others did not, such as TLI, NFI, CFI, and RMSEA, which showed a poor fit.